Tightening and untightening torque of M164M bolts: experimental and analytical study - Abdalla, Khairedin M.; Kaziolas, Dimitrios N.; Baniotopoulos, Charalambos C. (Journal of Structural Engineering, 2024)
The aim of the present paper is the investigation of the assembly behavior of high - strength bolts under friction. High - strength structural bolts assembly includes a bolt with hexagon head, a heavy nut and a hardened washer. To this end, an experimental procedure was carried out in order to evaluate the energy of high - strength bolts that is dissipated due to tightening and untightening. The total tested were 293 bolts, furnished to the requirements of AASHTO specifi cation M164M. The length of the bolts was 76 mm for 177 of them and 152 mm for the rest, while its diameter was M20 = 20mm. As far as the nuts are concerned, it is mentioned that 153 nuts of type 2H, 16 nuts of type DH, and 124 nuts of type C were used. The turn-of-nut tightening method is applied for the experimental evaluation of the tension and torque of bolt. Additionally the theoretically calculated preloading is compared with the experimental and the lost torque that overcomes friction calculated both theoretically and experimentally. It is found that the K-nut factor is affected by the type of the nut, the type of the lubricant and the length of the bolt. The percentage of tightening and untightening torque for both the theoretical and the experimental cases are almost identical.